2011
DOI: 10.1029/2010ja015916
|View full text |Cite
|
Sign up to set email alerts
|

Unusual nonlinear waves in the Venusian magnetosheath

Abstract: [1] Within the Venusian magnetosheath, Venus Express has observed the existence of high-amplitude, nonlinear waves which have been interpreted as large-scale nonlinear rotational structures within the magnetic field. A number of mechanisms have been proposed that can be used to explain their origin. Venus Express data have been searched for other examples of the similar structures. It appears that such structures are quite rare, being observed during only 8 of the dayside magnetosheath crossings among 676 that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…We can rule the vortices and coherent oscillations out of the generation mechanism for these waves. The vortices is formed by Kelvin‐Helmholtz instability due to the velocity shear between solar wind and ionospheric ions [ Pope et al ., ; Walker et al ., ], and they only exist in the downstream region of the Venusian bow shock. The coherent oscillations are caused by the spatial pressure variations due to gyrations of the directly transmitted ions downstream of the ramp [ Balikhin et al ., ; Ofman et al ., ], and they only exist in the downstream region of a quasi‐perpendicular shock with low Mach number and low β [ Balikhin et al ., ; Ofman et al ., ].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We can rule the vortices and coherent oscillations out of the generation mechanism for these waves. The vortices is formed by Kelvin‐Helmholtz instability due to the velocity shear between solar wind and ionospheric ions [ Pope et al ., ; Walker et al ., ], and they only exist in the downstream region of the Venusian bow shock. The coherent oscillations are caused by the spatial pressure variations due to gyrations of the directly transmitted ions downstream of the ramp [ Balikhin et al ., ; Ofman et al ., ], and they only exist in the downstream region of a quasi‐perpendicular shock with low Mach number and low β [ Balikhin et al ., ; Ofman et al ., ].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Due to the lack of an intrinsic magnetic field at Venus, there is a direct contact between the fast‐flowing solar wind and the Venusian ionosphere, and the velocity shear between the solar wind and the ions of ionopause is easy to be formed. The Kelvin‐Helmholz instability then grows in the Venusian magnetosheath [ Pope et al ., ; Walker et al ., ], especially near the terminator region [ Biernat et al ., ]. VEX has also observed coherent oscillations behind a quasi‐perpendicular shock under the conditions with low Mach number and low β [ Balikhin et al ., ], which are caused by the spatial pressure variations due to gyrations of the directly transmitted ions downstream of the ramp [ Balikhin et al ., ; Ofman et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that K‐H instability plays a significant role for ion loss from Venus. Recently, it was found a vortex like configuration detected in the magnetosheath in the VEX MAG data, and argued that it was a result of the K‐H instability [ Pope et al 2009; Walker et al , 2011]. Walker et al [2011] suggested that the waves were frequently observed when the upstream cone angle becomes lower than 40°.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of the upstream (downstream) waves is approximately 4.5 Hz (1.2 Hz) which compared to the local proton gyrofrequency of 0.6 Hz (1.95 Hz). There are a number of candidates for these waves such as whistler waves (Russell, ), ion cyclotron waves (Delva et al, ; Wei et al, ), and nonlinear magnetic structures (Walker et al, ). It is our interpretation that the waves upstream are Doppler‐shifted whistler mode waves as similar dispersive wave trains are commonly observed upstream of planetary bow shocks (Dimmock et al, ) with comparable characteristics.…”
Section: Vex Observationsmentioning
confidence: 99%